Saving a World Treasure: Protecting Florence from Flooding - Galloway Jr, Gerald Edward (Proceedings e report, 2017)
The Committee Firenze 2016, on the occasion of the 50th anniversary of the tragic 1966 flood, invited six engineers and scientists to form an International Technical Scientific Committee (ITSC) to assess the current status of flood protection for the city of Florence and identify steps to reduce the risk of flooding facing the city. In this final Report, ITSC concludes that Florence remains at risk to significant flooding and this risk grows each day. It is not a question of whether a flood of the magnitude of 1966 or greater will occur, but when. In fact, the level of protection that exists in Florence now is not on a level appropriate to the citizens and treasures that rest within the city. If, under current conditions, a 1966-like flood occurred, the consequences to human lives, treasures, properties and community infrastructure could be much more catastrophic than they were in 1966.